Pendampingan Implementasi Assessment for Learning dalam Mewujudkan Pembelajaran Berdiferensiasi pada Kurikulum Merdeka - Roqobih, Fikky Dian; Sudibyo, Elok; Subekti, Hasan; Purnomo, Aris Rudi; Rosdiana, Laily (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The goals of the Merdeka Curriculum is to meet each student’s unique and their needs of learning. Through differentiated learning, this could be put into practice. Assessment for Learning is a means to realize the differenciated learning. Nonetheless, a lot of teachers continue having trouble using this Assessment for Learning instrument, so this assistance activities are needed. These activities were carried out at SMPN in Pasuruan Regency which involved teacher association (MGMP) consisting of natural science teachers throughout Pasuruan Regency. The result of this activity is an improvement in science teachers' understanding regarding Assessment for Learning in the implementation of differentiated learning, shown by an increase in pretest and posttest scores. Apart from that, this mentoring activity also received a very good response from the activity participants.